Impact of caffeine on heart rate variability and fatigue indexes during recovery after endurance exercise: a crossover and double-blind study - Rahimi, Z.; Mehrabani, J.; Abdollahpour, S.; Nobari, H. (Trends in Sport Sciences, 2026)
Introduction: Caffeine increases heart rate by increasing sympathetic activity and it may also delay post-exercise cardiac recovery.